Test the characteristics of essential oils of fragrant Lemongrass stems and clove leaves as an electric mosquito repellent - Aisyah Suwaiya; Indah Lestari (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2020)
Essential oils from the stems of citronella and clove leaves contain chemical compounds, namely citronellal, eugenol, and geraniol, which function as mosquito killers. This study aims to make essential oils from fragrant lemongrass stems and clove leaves using the distillation method. Characteristic tests were carried out in the form of determining color, density, aroma resistance, and mosquito repellency of essential oils. The results of the color determination test showed that the essential oil from clove leaves was more brown in color and the density was greater than the essential oil from the citronella stem oil, while the durability of the aroma in the citronella oil was longer than that of the clove leaf oil. In testing the repulsion of mosquitoes, observations were made for 20 minutes to determine the number of dead mosquitoes, then the value of repulsion (DT) was calculated using probit analysis. The results of the mosquito repellent test showed that the DT value of the essential oil from the citronella stem was 60%-67%, the essential oil from the clove leaf was 54%-60%, while the mixture of the essential oil from the citronella stem and clove leaf was 67%-80 %. This shows that the essential oil from a mixture of citronella stems with clove leaves is able to kill mosquitoes better than only essential oils from citronella stems or clove leaves.©2020 JNSMR UIN Walisongo. All rights reserved.